Tessellated Scale, Ecualymnatus tessellatus (Signoret) (Insecta: Homoptera: Coccidae) - G. W. Dekle (EDIS)
Tessellated or palm scale is a soft scale that was first described in France by V. Signoret in 1873 from specimens collected on a palm he reported as Caryota ursus. The genus Eucalymnatus, according to Borchsenius (1957), contains 17 species; two species are Ethiopian in origin and the remainder neotropical. Borchsenius (1957) considers E. tessellatus (Sign.) probably South American in origin and disseminated by man to all parts of the world on its cultivated hosts. This document is EENY-090 (originally published as DPI Entomology Circular No. 138), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999.